Synthesis and Properties of an Electropolymer Obtained from a Dimeric Donor/Acceptor System with a 4,4′-Spirobi[cyclopenta[2,1-b:3,4-b′]dithiophene] Core - Orlandi, Simonetta (2015)
The design and synthesis of two potentially electropolymerizable electron donor-acceptor dyes characterized by a cruciform 4,4′-spirobi[cyclopenta[2,1-b:3,4-b′]dithiophene] core is here outlined. The new molecules feature two perpendicularly aligned cyclopentadithiophene branches, each one having an electrodimerizable, electron donor triphenylamine unit and an electron acceptor dicyanovinylene group. By merging these structural elements, the light absorption ability of the conjugated cyclopentadithiophene chromophore is extended to a broad region of the visible spectrum. The photoelectroactive film obtained from one of the dyes by electrochemical deposition technique retains the ability to generate photoinduced charge-separated states and to transport holes, turning this material into a unique example of donor-acceptor polymer with potential application in the development of organic optoelectronic devices. (Figure Presented).